Digital learning strategies in virtual educational environments - Flores-Rivera, Luis; Meléndez-Tamayo, Carlos (Revista Innova Educación, 2024)
Digital education has transformed the teaching-learning processes and mainly the teaching role. Indeed, its mission has evolved from being a builder, selector, and transmitter of knowledge to being a companion, mediator, and motivator in the construction of knowledge. In this sense, the research analyzes the digital learning strategies applied by the teacher in virtual educational environments. For this purpose, a quantitative and qualitative study was carried out on a group of 30 participating teachers who perfected their digital skills and socialized these in their educational field. The results show considerable appreciation of digital educational resources as a fundamental part of their digital strategies, as well as teaching skills and professional training. Finally, the research determined a high adaptation and integration of digital procedures to management and teaching work.
Keywords: education; educational strategies; computer-assisted instruction; skill; Information technology